Causal Inference by Independent Component Analysis: Theory and Applications*. (20th July 2012) - Moneta, Alessio; Entner, Doris; Hoyer, Patrik O.; Coad, Alex
Abstract Structural vector‐autoregressive models are potentially very useful tools for guiding both macro‐ and microeconomic policy. In this study, we present a recently developed method for estimating such models, which uses non‐normality to recover the causal structure underlying the observations. We show how the method can be applied to both microeconomic data (to study the processes of firm growth and firm performance) and macroeconomic data (to analyse the effects of monetary policy).